2019
DOI: 10.14529/mmp190103
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Intra-Chamber of Unsteady Turbulent Flows Stimulate. Part 1

Abstract: В работе представлена методика моделирования трехмерных внутренних нестационарных турбулентных течений, в частности, течения продуктов сгорания в твердотопливном ракетном двигателе. Приведена система определяющих уравнений, описывающая поток сжимаемого вязкого газа, записанная в цилиндрической системе координат. Предложен вычислительный алгоритм, разработанный на основе модифицированной схемы расщепления векторов потоков, относящийся к классу методов, использующих подход Годунова. Данный алгоритм пригоден для … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…These gas dynamic equations are supplemented by the equations of the k-turbulence model. A more detailed mathematical setting can be found in [16,25].…”
Section: Gas Dynamics Of Real Gas In a Safety Valve Using The Godunov Schemementioning
confidence: 99%
“…These gas dynamic equations are supplemented by the equations of the k-turbulence model. A more detailed mathematical setting can be found in [16,25].…”
Section: Gas Dynamics Of Real Gas In a Safety Valve Using The Godunov Schemementioning
confidence: 99%
“…Mathematical modeling of intrachamber processes in a power plant is considered in [14][15][16][17][18][19][20][21]. However, they lack practically useful criteria equations.…”
Section: Introductionmentioning
confidence: 99%
“…However, they lack practically useful criteria equations. In [13][14][15][16][17][18][19][20], it is shown that the spatial flow in the CC and PV is characterized by the presence of vortex structures. Heat exchange processes in different layouts of PP are studied in [15][16][17], but they do not provide criteria relations, and there is no assessment of the applicability for equations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations